2013
DOI: 10.1111/bjd.12422
|View full text |Cite
|
Sign up to set email alerts
|

Survival rate of antitumour necrosis factor-α treatments for psoriasis in routine dermatological practice: a multicentre observational study

Abstract: SummaryBackground Adherence is an overall marker of treatment success, and it depends on multiple factors including efficacy and safety. Despite the wide use of tumour necrosis factor (TNF)-a blockers in the treatment of plaque-type psoriasis, few data regarding treatment adherence in routine clinical practice are available. Objectives To estimate the long-term survival rate of anti-TNF-a therapy in a cohort of patients with psoriasis in routine clinical practice; to evaluate the reasons for and predictors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
156
11
18

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(214 citation statements)
references
References 19 publications
29
156
11
18
Order By: Relevance
“…Thirteen observational studies with 17,444 patients reported on the comparative risk of discontinuation of TIMs due to AEs (see Supplementary Table 1, available Six observational studies reported only crude rates of discontinuation and did not provide comparative estimates (22)(23)(24)(25)(26)(27). These studies generally observed a higher proportion of patients discontinuing infliximab than adalimumab, etanercept, or anakinra treatment due to AEs in CD, RA, and plaque psoriasis.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen observational studies with 17,444 patients reported on the comparative risk of discontinuation of TIMs due to AEs (see Supplementary Table 1, available Six observational studies reported only crude rates of discontinuation and did not provide comparative estimates (22)(23)(24)(25)(26)(27). These studies generally observed a higher proportion of patients discontinuing infliximab than adalimumab, etanercept, or anakinra treatment due to AEs in CD, RA, and plaque psoriasis.…”
Section: Resultsmentioning
confidence: 99%
“…Even though the disease is currently not curable, there are a number of therapeutic options which ensure a symptom-free status, although requires a long term, often lifelong treatment (3,4). Optimal drug survival is fundamental in the management of psoriasis and comorbidities (5).…”
Section: Introductionmentioning
confidence: 99%
“…Drug survival, that is, persistence, is a comprehensive measure of therapeutic success, which depends on a variety of factors, including efficacy, safety, tolerability and patient satisfaction (5). Suboptimal persistence is a common and complex problem among patients with chronic diseases, including psoriasis (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…However, while biologics are generally very effective, 27% of patients treated with TNFα inhibitors were found to discontinue treatment after 29 months due to lack of initial efficacy (primary failure), loss of efficacy over time (secondary failure), or intolerance 32. Therefore, strategies are needed to maintain efficacy with acceptable tolerability.…”
Section: Considerations For Switching Therapymentioning
confidence: 99%